PREPARASI KARBON AKTIF DARI BERBAGAI JENIS BAMBU DAN KEMAMPUANNYA DALAM ADSORPSI UAP AIR DI DALAM UDARA - , MUSTIKA DEWI MASITHOH, Dra. Ani Setyopratiwi, M,Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Have performed preparation activated carbon from various kinds of bamboo using chemical and physical activation with KOH and by heating under 600 Â°C and N2 flow of 30 mL/min for 1 hour. The objective of this study is to characterize activated carbon obtained from bamboo as a precursor on water vapour adsorption under humid condition. Activated carbon was then analysed with surface area analyser, scanning electron microscopy, and fourier transform infrared (FT-IR) apparatus. The quality of the produced activated carbon was found to be acceptable under SII 0258-88 standard. Water vapour adsorption was then carried out under relative humidity of 50-90 %. The results show that activated carbon has an ash content of 4.76-11.30%, water content of 1.64-6.87%, iodine number of 237.30-357.22 mg/g. Petung activated carbon has a surface area of 260 m2/g, pore volume of 0.1618 cc/g and pore radius of 15.193 Ã. Water vapor adsorption is related to the pore properties and availability of functional groups on the surface of activated carbon. Petung activated carbon shown the best water vapor adsorption around 0.148 g/g under relative humidity of 90%